Lycopene and resveratrol pretreatment did not interfere with the liver of hepatectomized rats - Barros,Pedro Paulo (2017)
Abstract Purpose: To investigate the effects of lycopene and resveratrol pretreatment on hepatic hyperplasia in partially hepatectomized rats. Methods: The lycopene group and the resveratrol group received 40 mg/kg/day of lycopene or resveratrol, respectively (dissolved in olive oil or in saline solution, respectively) and administered via a gastric tube for 30 days. The partially hepatectomzed (PH) control groups received saline or olive oil via a gastric tube for 30 days, respectively, and the normal control group received no treatment. Liver tissue and intracardiac blood samples were obtained 24, 36 or 48 h after PH. Results: No areas of fibrosis were detected. No significant changes in mitotic index, in the number of apoptosis events or in aspartate aminotransferase and alanine aminotransferase levels were observed. Conclusions: Lycopene and resveratrol pretreatment did not interfere on hepatic hyperplasia in partially hepatectomized rats.